2017
DOI: 10.5588/pha.17.0026
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of two active case finding approaches for detection of tuberculosis in Bandung City, Indonesia

Abstract: A community health clinic catchment area in the eastern part of Bandung City, Indonesia. To evaluate the feasibility of two different screening interventions using community health workers (CHWs) in detecting tuberculosis (TB) cases. This was a feasibility study of 1) house-to-house TB symptom screening of five randomly selected 'neighbourhoods' in the catchment area, and 2) selected screening of household contacts of TB index patients and their neighbouring households. Acceptability was assessed through focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Early detection helps to reduce the risks of TB transmission, poor treatment outcomes, undesirable health sequelae, and adverse social and economic consequences of the disease [12]. Studies have shown that community-based systematic screening of HH contacts is feasible and can contribute to improve TB cases finding [13][14][15][16], but it is not practiced in many high burden countries [17].…”
Section: Introductionmentioning
confidence: 99%
“…Early detection helps to reduce the risks of TB transmission, poor treatment outcomes, undesirable health sequelae, and adverse social and economic consequences of the disease [12]. Studies have shown that community-based systematic screening of HH contacts is feasible and can contribute to improve TB cases finding [13][14][15][16], but it is not practiced in many high burden countries [17].…”
Section: Introductionmentioning
confidence: 99%
“…Extraordinary efforts are required to achieve the target of hundred-thousand inoculation per day and increase the number of healthcare staff up to more than seven times the current number within a limited, tight time. One plausible strategy is the involvement of community health workers who are familiar with child vaccination or tuberculosis program [ 15 ]. In low- and middle-income countries, the problem is beyond the healthcare staff availability.…”
Section: Discussionmentioning
confidence: 99%
“…However, we now know that in most high burden settings, the majority of Mycobacterium tuberculosis (Mtb) transmission occurs in the community where there are vastly greater numbers of human encounters [5] that often share socio-economic risk factors that are correlated with TB [6,7]. In a feasibility study in Bandung, Indonesia [8] we followed individual TB patients back to their communities. We found an incidence rate of self-reported TB of 649 per 100,000/year in TB household contacts, 675 in neighbouring households, and 325 in randomly selected neighbourhoods [8].…”
Section: Introductionmentioning
confidence: 99%
“…In a feasibility study in Bandung, Indonesia [8] we followed individual TB patients back to their communities. We found an incidence rate of self-reported TB of 649 per 100,000/year in TB household contacts, 675 in neighbouring households, and 325 in randomly selected neighbourhoods [8].…”
Section: Introductionmentioning
confidence: 99%